2006
DOI: 10.1111/j.1523-1739.2006.00557.x
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Avian Feeding Guilds to Tropical Forest Disturbance

Abstract: Anthropogenic habitat disturbance is a major threat to tropical forests and understanding the ecological consequences of this disturbance is crucial for the conservation of biodiversity. There have been many attempts to determine the ecological traits associated with bird species' vulnerability to disturbance, but no attempt has been made to synthesize these studies to show consensus. We analyzed data from 57 published studies (covering 1214 bird species) that investigated the response of tropical bird assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
205
3
27

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(252 citation statements)
references
References 42 publications
17
205
3
27
Order By: Relevance
“…These results are consistent with previous studies of birds on impacts of commercial selective logging [91,92] and fragmentation [53] showing that avian feeding guilds differed in their sensitivity to habitat disturbance, and that granivores were least affected. The sensitivity of avian carnivores and predatory ants to fragmentation may reflect their relatively high trophic status, for example, if their feeding requirements mean they have large minimum-area requirements for persistence.…”
Section: Discussion (A) Comparisons Of Sars Among Taxasupporting
confidence: 83%
See 1 more Smart Citation
“…These results are consistent with previous studies of birds on impacts of commercial selective logging [91,92] and fragmentation [53] showing that avian feeding guilds differed in their sensitivity to habitat disturbance, and that granivores were least affected. The sensitivity of avian carnivores and predatory ants to fragmentation may reflect their relatively high trophic status, for example, if their feeding requirements mean they have large minimum-area requirements for persistence.…”
Section: Discussion (A) Comparisons Of Sars Among Taxasupporting
confidence: 83%
“…The sensitivity of avian nectarivores to habitat fragmentation that we detected may reflect that they are generally small specialist species with restricted ranges, which might be expected to be more adversely affected by fragmentation ( [24,93]; but see [53]). In contrast, avian granivores and some guilds of ants may be able to exploit resources in matrix habitats [91].…”
Section: Discussion (A) Comparisons Of Sars Among Taxamentioning
confidence: 99%
“…Berry et al 2010;Edwards et al 2011) many taxa are strongly affected by disturbance. For example, a review of bird responses to tropical forest disturbance (Gray et al 2007) found significant declines in richness and abundance of insectivores, omnivores and frugivores, although increases in granivores. Also, a review of tropical forest dung beetle communities showed similar diversity declines with increasing habitat disturbance, along with a reduction in the number of forest species (Nichols et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Post-fragmentation bird communities are often unevenly structured, being dominated by few species. Moreover, the fact that bird species consume a variety of food items means that responses to habitat disturbances differ, depending on feeding guild (Gray et al 2007). Insectivorous and frugivorous birds have been shown to be more strongly affected by forest fragmentation (Sodhi et al 2004b) than other major feeding guilds.…”
Section: Introductionmentioning
confidence: 99%